Secrecy, self-blame and risks for social exclusion—Family members’ experiences of gambling problems in Japan - Takiguchi, Naoko; Kawanishi, Yuko; Samuelsson, Eva (Frontiers in Psychiatry, 2022)
The predominant gambling policy to respond to the adverse consequences of excessive gambling has been the Reno Model, which places the responsibility for gambling-caused problems on gamblers themselves. The newly implemented Japanese gambling policy, which shares basic premises with the Reno Model, focuses on the individual pathology of gamblers. However, this model lacks other critical perspectives: environmental and structural factors. To fully understand the harms caused by gambling; it is important to also pay attention to the negative consequences for affected others. In this brief report, we explore family members’ experiences of gambling problems within the specific context of the Japanese gambling policy. Interviews with family members reveal self-stigma of being bad parents which elicits shame and efforts to maintain secrecy, as well as public stigma involving labeling, isolation, risks of status loss, social exclusion and discrimination. The focus on individual pathology in Japanese legislation as well as in public and professional perception, reinforces self-blame, anxiety and remorse on the part of affected family members. When contrasted with the lived experiences of gamblers’ family members, the inconsistencies and unreasonableness of the individual pathology paradigm in Japanese gambling policy become evident. It is necessary to shift the focus of gambling policies from individual to socio-political-cultural factors, investigating how these factors influence gambling-caused harm, especially in the Japanese context.